Adsorption of methane on the hydrophobic surface of methyl silica in isobaric conditions - Turov, V.V.; Gunko, V.M.; Krupskaya, T.V. (Reports of the National Academy of Sciences of Ukraine, 2023)
Low-temperature 1H NMR spectroscopy was used to study the adsorption of methane on a surface of hydrated hydrophobic silica AM-1-300. It is shown that the adsorption value depends strongly on the hydration and pretreatment of samples. The maximum adsorption of methane (up to 80 mg/g) is observed for a sample rehydrated (h = 0.2 g/g) after complete drying. It is found that methane adsorption is determined by several bound water clusters of R < 2 nm in radius. Based on the shape of the temperature dependence of the methane adsorption, it is assumed that there is both physical adsorption and the formation of solid methane hydrates.